Religious and cultural influences on the selection of menu - Jamaludin, Mohammad Aizat; Abd Rahman, Nur Diyana; Ahmad Fadzillah, Nurrulhidayah; Ramli, Mohd Anuar (Elsevier Ltd., 2018)
Preparation and Processing of Religious and Cultural Foods covers the production and processing of foods from major religions, focusing on the intersection of religion, science and cultural perceptions in the production and processing of modern religious and vegetarian foods. Quality control and authentication technologies are looked at in-depth, while nutrition, antioxidants, aging, hygiene and other long-term health factors are presented from a scientific standpoint. Bringing together the top scientific researchers on this essential topic of importance to a huge percentage of the world’s population, this book is ideal for food company innovation and R&D managers, producers and processers of religious foods. Religious groups have often been slow in implementing recent science and technology breakthroughs employed in the preparation, processing and packaging of various foods. This book provides a culturally sensitive coverage of these areas with an aim to encourage advancement.